Dragons in a bag - Elliott, Zetta (Random House Books for Young Readers, 2018)
In Brooklyn, nine-year-old Jax joins Ma, a curmudgeonly witch who lives in his building, on a quest to deliver three baby dragons to a magical world, and along the way discovers his true calling.